The fly route of extended-spectrum-β-lactamase-producing Enterobacteriaceae dissemination in a cattle farm: from the ecosystem to the molecular scale - Caderhoussin, Alann; Couvin, David; Gruel, Gaëlle; Quétel, Isaure; Pot, Matthieu; Arquet, Rémy; Dereeper, Alexis; Bambou, Jean-Christophe; Talarmin, Antoine; Ferdinand, Séverine (Frontiers in Antibiotics, 2024)
This study attempts to explain previous findings showing a hotspot of multidrug-resistant E. coli in food-producing cattle from a farm that does not use third-generation cephalosporins. Given the close contact between humans and livestock, it was important to understand the origin and maintenance of these multidrug-resistant isolates. By combining classical bacteriology, high-resolution molecular biology and bioinformatics approaches, we found that flies and antibiotic selective pressure are sources of contamination and maintenance of antibiotic resistance in our ecosystem. Although transmission to humans is still hypothetical, circulating strains share and exchange resistance genes via plasmids. This is the first observation of human-derived resistance determinants clustering in animals in Guadeloupe. Thus, our study presents important breakthroughs in the area of antibiotic resistance and mobile genetic elements in the field of microbiology at the frontiers of human and animal health relevant to the specialty section. In addition, we have identified critical points where hygiene measures need to be strengthened, and then made recommendations to breeders to improve the sanitary quality of their animals and the health of their workers. With a direct impact on farm management and human health, our research is resolutely focused on benefiting humankind, in line with the Frontiers philosophy.